2019
DOI: 10.1016/j.jemermed.2019.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Patients Who Leave the Emergency Department Without Being Seen and Their Follow-Up Behavior: A Retrospective Descriptive Analysis

Abstract: Background: Past studies suggest that patients who leave without being seen by a physician (LWBS) from a hospital's emergency department (ED) represent a quality and safety concern, and thus LWBS rates have often been used as an ED performance metric.There are few recent studies, however, that have examined the characteristics of the LWBS population at hospitals in the United States.Objectives: This study describes the LWBS population at a multi-hospital academic health system.Methods: This was a retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…An association with poverty (which we found by analyzing subjects from zip codes with lower household incomes) was corroborated by a study by Hsia et al 5 Some studies have shown an urban location of patients in proximity to the hospital 22 to be a significant factor, but this was refuted by our analysis. Similar to our analysis, other studies have pointed out lower acuity at presentation to have a significant association with LWBS, 6,18,23 but no scholars have studied relationships with the presence of chronic conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…An association with poverty (which we found by analyzing subjects from zip codes with lower household incomes) was corroborated by a study by Hsia et al 5 Some studies have shown an urban location of patients in proximity to the hospital 22 to be a significant factor, but this was refuted by our analysis. Similar to our analysis, other studies have pointed out lower acuity at presentation to have a significant association with LWBS, 6,18,23 but no scholars have studied relationships with the presence of chronic conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Adjusting for these might have created better models. Finally, the data available did not allow us to analyze the time from a previous visit or to identify high users of EDs, both of which have been shown to be important LWBS predictors 18 …”
Section: Resultsmentioning
confidence: 99%
“…Leave without being seen (LWBS) was defined as leaving the ED before consulting a physician after triage. LWBS is one of the factors reflecting the failure of the ED process, long waiting times, and ED overcrowding [ 10 , 11 ]. LWBS results in a higher chance of revisitation, since patients’ problems are often left unresolved [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, for longer-term sustainability, performance-based outcome metrics are needed to assess the impact of telehealth on health systems. A few studies have made initial attempts to apply existing performance metrics to assess telehealth implementation [36,37]. The outcome measures we propose (Table 2) can help guide future work in optimizing and scaling telehealth implementation.…”
Section: Discussionmentioning
confidence: 99%